The measurement of changes in distributional preferences - Cui, Chi; Dai, Ming; Alevy, Jonathan E. (AWI discussion paper series, 2025)
This study explores the way in which social information about giving impacts the stability of distributional preferences. We designed a two-stage treatment which varied the information participants received about the maximum amounts given to recipients. Information on maximum giving can significantly increase giving share compared to the control group, especially when the relative price of giving is low. However, with a rise in the relative price,the giving decreases significantly. Applying measures of consistency with the Generalized Axiom of Revealed Preference (GARP) and non-linear Tobit estimates of preferences, we observe changes in distributional preferences indicating that more fairness and efficiency are considered in distributions when social information is provided. Type changes in distributional preferences at an individual level provide evidence that there is one substitution relationship with context to fairness-selfishness and efficiency-equality tradeoffs. People’s preferences can change due to environmental factors, which are less equalityfocused and more efficiency-oriented. It provides evidence for heterogeneity in preference stability by studying distribution stability causal effect.